James: an exegetical guide for preaching and teaching - Bateman, Herbert W. (Big Greek Idea Series., 2022)
To read the Greek text of James is to face a rugged style and brief phrasing that match the fervency of the letter's meaning. The book of James powerfully exhorts the earliest Christian believers to faithful living. Biblical Greek experts Herbert W. Bateman IV and William C. Varner lay out the linguistic and grammatical features unique to James--such as his specialized vocabulary and prolific use of imperatives--to show how the book's many strong statements connect to one another in this masterwork on living according to the teachings of Jesus